Copper(II) removal potential from aqueous solution by pyrolysis biochar derived from anaerobically digested algae-dairy-manure and effect of KOH activation. Issue 1 (March 2016) - Jin, Hongmei; Hanif, Muhammad Usman; Capareda, Sergio; Chang, Zhizhou; Huang, Hongying; Ai, Yuchun
Abstract: Biochar produced from waste products is being considered as an alternative adsorbent for removal of aqueous heavy metals. In this work, experimental and modeling investigations were conducted to examine the effect of biochars pyrolyzed from anaerobically digested algae-dairy-manure slurry (DAS) on removing aqueous Cu(II) before and after activated by 2 M KOH solution. Results showed that the highest adsorption capacity of pristine biochars was 21.12 mg/g. The Elovich model and Freundlich adsorption isotherm model can preferably describe the adsorption process, which indicated that Cu(II) was chemisorbed on heterogeneous surface of DAS-derived biochars. The activated biochar showed enhanced Cu(II) adsorption ability with an adsorption capacity of 50.71 mg/g, which was more than 3.36 times of pristine biochars. Increase of surface area and changes of porous texture, especially the functional groups on the surface of activated biochars are the major contributors to its more efficient adsorption of Cu(II).